Fenomenologi Komunikasi Pada Ritual Megengan di Desa Wonosunyo Kecamatan Gempol Kabupaten Pasuruan - Baiq Helda Maylinda Afandi; M Rifai (Brand Communication, 2024)
This research aims to understand the phenomenology of communication in Megengan ritual in Wonosunyo Village, Gempol District, Pasuruan Regency. Megengan ritual is a tradition of Javanese people which is held to welcome the month of Ramadan, involving various symbols and communication practices that are rich in cultural meaning. The method used in this research is qualitative with a phenomenological approach, where data is collected through participatory observation, in-depth interviews, and documentation analysis. The results of this study show that communication in the Megengan ritual plays an important role in strengthening cultural identity, building community solidarity, and teaching moral values to the younger generation. Through this ritual, the people of Wonosunyo Village can maintain their traditions in the midst of modernization, while maintaining social cohesion and local cultural sustainability.